Risk factors for stent graft thrombosis after transjugular intrahepatic portosystemic shunt creation - Jahangiri, Younes; Kerrigan, Timothy; Li, Lei; Prosser, Dominik; Brar, Anantnoor; Righetti, Johnathan; Schenning, Ryan C.; Kaufman, John A.; Farsad, Khashayar (Cardiovascular Diagnosis and Therapy, 2017)
Background: To identify risk factors of stent graft thrombosis after transjugular intrahepatic portosystemic shunt (TIPS) creation. Methods: Patients who underwent TIPS creation between June 2003 and January 2016 and with followup assessing stent graft patency were included (n=174). Baseline comorbidities, liver function, procedural details and follow-up liver function tests were analyzed in association with hazards of thrombosis on followup. Competing risk cox regression models were used considering liver transplant after TIPS creation as the competing risk variable. Results: One-, 2- and 5-year primary patency rates were 94.1%, 91.7% and 78.2%, respectively. Patient age [sub-hazard ratio (sHR): 1.13; P=0.001], body mass index (BMI)